(untitled) (Journal of Geography and Environmental Management, 2019)
The article deals with the territorial differences between the administrative districts of West Kazakhstan in terms of morbidity. Correlation between environmental factors and disease groups in the population. The result of the work is to conduct zoning of West Kazakhstan region generally rated health.